Gastrointestinal nematode infections do not hinder the development of simmental x nellore crossbred calves raised with a nutritionally enhanced diet - Das Neves, José Henrique; Carvalho, Nadino; Amarante, Alessandro Francisco Talamini Do [UNESP] (FapUNIFESP (SciELO), 2020)
An evaluation was made of the effect of anthelmintic treatments on the performance of Simmental X Nellore crossbred calves before and after weaning. To this end, the calves were divided into three groups: (1) treated monthly with a low efficacy anthelmintic drug, ivermectin; (2) treated monthly with a highly effective anthelmintic drug, albendazole; and (3) untreated control group. All the groups in this experiment showed an average fecal egg count of less than 400 eggs per gram (EPG), and no clinical signs of parasitic gastroenteritis. The blood variables were within the normal range and no calf presented anemia. In most of the samplings, mean EPGs were significantly lower (P<0.05) in the group treated with albendazole. The calves received dietary supplementation before and after weaning, which enabled them to gain weight in every month of the experiment and reach a body weight of about 250 kg on the last sampling date, before turning one year old. The anthelmintic treatments did not affect body weight gain, leading to the conclusion that, when fed with suitable dietary supplements, Simmental X Nellore crossbred calves are not affected by gastrointestinal nematode parasites acquired by grazing.
Infecções por nematódeos gastrintestinais não prejudicam o desenvolvimento de bezerros simental x nelore criados em plano nutricional elevado
Keywords: Albendazole; Cattle; Haemonchus; Ivermectin; Nutrition